what drives the receipt of zakat fund? A Time Series Evidence from Indonesia - Riska Nur Istiqomah; Laila Masruro Pimada (NUsantara Islamic Economic Journal, 2023)
Indonesia as a country with the majority of Muslim population can take advantage of zakat instrument in order to solve macroeconomic problems like poverty case. The potential of zakat in Indonesia since 2017-2021 tends to increase. This condition is in line with an increase in the number of Muslim populations, however the realization of zakat receipt is not still comparable to the targeted potential. One of factors that cause the receipt of zakat is not optimal yet in Indonesia is macroeconomic factor that might affect public welfare which is related to economic stability of the country. Therefore, this research is aimed to identify short and long-term effects of economic growth, inflation, exchange rate, and money supply on receipt of zakat in Indonesia. The method in this research is quantitative method with VECM analysis. This research uses time series data with the period from 2017-2021. The variables in this research comprise of independent variables: economic growth, inflation, exchange rate, and money supply, while dependent variable is receipt of zakat. The research result refers that within short-term and long-term, the variables of economic growth and inflation affect negatively and significantly to zakat receipt. Meanwhile, the short-term exchange rate and money supply do not have significant effects to zakat receipt, while in the long-term; they have positive and significant effects.